Functional characterisation of glutathione export from the rat lens. (January 2018) - Umapathy, Ankita; Li, Bo; Donaldson, Paul J.; Lim, Julie C.
Abstract: In this study, we have investigated whether the lens was capable of exporting the antioxidant glutathione. Pairs of rat lenses were cultured in isosmotic artificial aqueous humour for one, two, three, or six hours in low oxygen conditions (90% N2, 5% CO2, 5% O2 ), and reduced glutathione (GSH) and oxidised glutathione (GSSG) levels measured in the media and lenses. We show that the rat lens is capable of releasing ∼5 nmol GSH for each time point suggesting that GSH release is regulated since it does not appreciably increase over time. We also demonstrated that the predominant form of glutathione released was the reduced form. We next cultured lenses in the absence or presence of acivicin, a γ-glutamyl transpeptidase (GGT) inhibitor, and found that GSH levels were significantly increased (p < 0.001) in the presence of this inhibitor, which indicated that GSH released by the lens undergoes degradation into its constituent amino acids. GSH release was significantly decreased (p < 0.001) in the presence of 100 μM MK571, a multidrug resistance-associated protein (Mrp) inhibitor, suggesting that Mrp transporters mediate GSH efflux from the lens. Culturing lenses in low (10 μM) or high (70 μM) concentrations of H2 O2 for one hour significantly increased total glutathione levels (p < 0.05) relative to controls, due to the increased release of GSSG. Our results show that in response to oxidative stress, the rat lens is able to release GSH or GSSG, thereby serving to maintain lens redox state or potentially influence the redox state of nearby tissues. Highlights: We cultured rat lenses in low O2 and measured glutathione levels in the media. We show that the lens can export reduced glutathione (GSH) via multidrug resistance-associated proteins. Under oxidative stress, the lens predominantly releases oxidised glutathione (GSSG). These studies show that the lens can influence the composition of the ocular humors. This allows for maintenance of the GSH/GSSG redox state of the lens and nearby tissues.